The The Influnce of Tiktok Marketing Content on Skintific Brand Image - Kezia Angelique RIWONG; Hilda Yunita WONO (PT Keberlanjutan Strategis Indonesia, 2024)
In the digital age, social media has become an essential part of daily life, revolutionizing communication. In 2023, Indonesia saw a significant rise in social media users, reaching 167 million. This growth has notably impacted various areas, particularly business marketing. TikTok, a popular platform known for its user-friendly algorithm, has been utilized by brands like SKINTIFIC, a skincare company, for marketing purposes in Indonesia. Researchers are intrigued by whether SKINTIFIC's TikTok marketing content affects its brand image. This study employs a descriptive quantitative approach, focusing on the correlation between TikTok marketing content and SKINTIFIC's brand image, based on marketing and brand image theories. Using simple linear regression analysis, the study finds that TikTok marketing content influences brand image by 53%. Consequently, SKINTIFIC is recommended to enhance its TikTok marketing content to bolster its brand image